Examining Digital Activism through Sentiments for Feminism Issues on Instagram (Case Study @perempuanberkisah) - Lasmery Girsang; Tesalonika Hasugian (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2025)
The high number of sexual violence cases against women in Indonesia remains alarming, with a recent surge in gender-based cyber violence that exploits victims through sexual content. This phenomenon prompted the author to investigate how the Instagram account @perempuanberkisah manages public narratives and responses from netizens toward stories shared by women victims of sextortion. The main objective of this research is to analyze the sentiment and discourse dynamics generated in the comment sections of this platform. Employing a qualitative approach with a case study design, the study selected three sextortion-related posts from @perempuanberkisah during 2023. Sentiment analysis was also conducted to categorize the direction of netizen comments into positive, negative, and neutral. The findings reveal that neutral sentiments dominate the discussions, surpassing positive and negative sentiments across all three posts. This suggests that while @perempuanberkisah serves as a platform for raising awareness and empowering victims, netizen engagement tends to remain cautious and reflective rather than explicitly supportive or oppositional. Theoretically, this study enriches feminist perspectives on digital activism and online narrative management. Practically, it highlights the importance of safe online spaces for survivors. Future research is encouraged to explore similar issues using additional theoretical frameworks and comparative platforms.